Woman between islam and western society - Khan, Maulana Wahiduddin; Khanam, Dr. Fari ([S.l.] : Goodword, EBook Edition: Viqar Alam, 2000)
To interpret the Islamic concept of woman as (3z(Bdegradation(3y (Bof woman is to distort the actual issue. Islam has never asserted that woman is inferior to man: it has only made the point that woman is differently constituts
Kindle eBook.